Deficient Resident Memory T Cell and CD8 T Cell Response to Commensals in Inflammatory Bowel Disease. (26th October 2019) - Noble, Alistair; Durant, Lydia; Hoyles, Lesley; Mccartney, Anne L; Man, Ripple; Segal, Jonathan; Costello, Samuel P; Hendy, Philip; Reddi, Durga; Bouri, Sonia; Lim, Dennis N F; Pring, Toby; et al.
Abstract: Background and Aims: The intestinal microbiota is closely associated with resident memory lymphocytes in mucosal tissue. We sought to understand how acquired cellular and humoral immunity to the microbiota differ in health versus inflammatory bowel disease [IBD]. Methods: Resident memory T cells [Trm] in colonic biopsies and local antibody responses to intraepithelial microbes were analysed. Systemic antigen-specific immune T and B cell memory to a panel of commensal microbes was assessed. Results: Systemically, healthy blood showed CD4 and occasional CD8 memory T cell responses to selected intestinal bacteria, but few memory B cell responses. In IBD, CD8 memory T cell responses decreased although B cell responses and circulating plasmablasts increased. Possibly secondary to loss of systemic CD8 T cell responses in IBD, dramatically reduced numbers of mucosal CD8 + Trm and γδ T cells were observed. IgA responses to intraepithelial bacteria were increased. Colonic Trm expressed CD39 and CD73 ectonucleotidases, characteristic of regulatory T cells. Cytokines/factors required for Trm differentiation were identified, and in vitro-generated Trm expressed regulatory T cell function via CD39. Cognate interaction between T cells and dendritic cells induced T-bet expression in dendritic cells, a key mechanism in regulating cell-mediated mucosal responses. Conclusions: A previously unrecognised imbalance exists between cellular and humoral immunity to the microbiota in IBD, with loss of mucosal T cell-mediated barrier immunity and uncontrolled antibody responses. Regulatory function of Trm may explain their association with intestinal health. Promoting Trm and their interaction with dendritic cells, rather than immunosuppression, may reinforce tissue immunity, improve barrier function, and prevent B cell dysfunction in microbiota-associated disease and IBD aetiology.